Cross-cutting best practices for new product development (NPD) in turbulent environments: the effects of integration and co-creation - Mateus Panizzon; Gabriel Vidor; Maria Emília Camargo (Innovation & Management Review, 2022)
Purpose - Continuous understanding of the best practices associated with new product development is a constant research opportunity to advance knowledge in the field, as far as changes in the business environment and the increasing turbulence level in different market segments create and reposition the importance of practices over time. Design/methodology/approach - Based on a systematic review, the study aimed to analyze the 100 most relevant articles published in international journals on new product development (NDP), identifying new patterns on the best practices for new product development and the types of relationship involved in NPD. Findings - Among the several practices observed in the literature, the analysis point to a larger group of studies that converge on the identification of a positive and significant relationship in integration - simultaneously - between supplier, company, customers and strategic alliances and the performance of NPD. Research limitations/implications - These results support integration as a cross-cutting and structural best practice for NPD, as long as it is constituted as a capacity, mainly applied in highly turbulent environments. This approach supported the proposition of a new framework. Practical implications - Organizations will be able to implement the proposed framework to NPD strategy in order to prioritize resources in best practices, aiming to increase the performance of new product development. Social implications - The adoption of integration and co-creation practices for the development of new products expands the possibilities of economic and social development, based on the involvement of the actors in this network. Originality/value - This model had not yet been proposed in the literature, filling a gap in the agenda for future studies.
Keywords: 650; Best practices; Co-creation; Digital transformation; Integration; New product development